The hegemony of the 'despots': the control of avifaunas over vast continental areas. Issue 9 (15th April 2014) - Mac Nally, Ralph; Kutt, Alex S.; Eyre, Teresa J.; Perry, Justin J.; Vanderduys, Eric P.; Mathieson, Michael; Ferguson, Daniel J.; Thomson, James R.; Andersen, Alan
Abstract Aim We explored whether one native bird (the yellow‐throated miner Manorina flavigula) greatly affected the composition of avifaunas in > 500, 000 km2 in northern Australia. Location Rangelands of north‐eastern Australia Methods Repeated avian surveys were conducted in 368 locations, for which in‐site vegetation and landscape‐contextual measurements were made. Hierarchical Bayesian models were used to determine whether avian assemblages were affected by variation in abundances of the yellow‐throated miner. Results Variation in the abundances of the yellow‐throated miner appeared to be governed largely by vegetation cover in surrounding landscapes. Summed abundances and richness of birds less massive than the yellow‐throated miner (< 53 g) were negatively associated with abundances of the yellow‐throated miner. Variation in other widely distributed species with larger body masses than the yellow‐throated miner (> 53 g) bird could not explain the patterns of variation in small‐bodied species as well as the yellow‐throated miner. There were no relationships between abundances and richness of larger species and abundances of the yellow‐throated miner. Main conclusions The genus Manorina appears to be a competitive despot insofar as species smaller than it are concerned. There now is strong evidence that the local composition of avifaunas over much of a continent is controlled by the indiscriminate aggression of a colonial genus. Many of the existing ideas in community ecology that have been proffered for explaining the composition of vertebrate assemblages are inadequate for these assemblages given the profound influence of species of the genus Manorina. The mooted agricultural expansion of development in northern Australia almost certainly would favour the spread of the yellow‐throated miner and probably will depress the occurrence and abundances of small‐bodied bird species.